"Only a Friend": The Bereavement Process of Young Adults After the Loss of a Close Friend in an Extreme Terror Incident—A Qualitative Approach. (November 2016) - Johnsen, Iren; Dyregrov, Kari
Friendships are very important for human beings, and especially for young people, but few studies have explored the consequences of losing a close friend. To identify and help this often overlooked population of bereaved, we need more knowledge of their bereavement processes. This study is part of a larger longitudinal study which aims to increase awareness of bereaveds' situation after the killings at Utøya, Norway, July 22, 2011. Qualitative in-depth interviews were conducted with 13 young adults on the experiences of losing their close friend. Themes identified were how circumstances of the event complicate the grieving, the daily experiences of the loss, and recognition of friends as bereaved. Findings show that the loss of a close friend has had a profound effect on the young people, and the loss of a friend is also a distinct loss that is not comparable to other losses.